Prognostic significance of FOXM1 in oral squamous cell carcinoma patients treated by docetaxel-containing regimens - Harada, Koji (Mol Clin Oncol, 2019)
Forkhead box protein M1 (FOXM1) is an oncoprotein that is involved in cell proliferation, differentiation and aging, and overexpression of FOXM1 is thought to be associated with the development and progression of various types of cancer. The expression of FOXM1 was retrospectively examined in tumor tissues taken from 56 oral squamous cell carcinoma (OSCC) patients by immunohistochemical staining. All of these patients received docetaxel (Doc)-containing regimens as treatments against OSCC. The association between FOXM1 expression and the clinicopathological characteristics and prognosis of these patients was then examined. FOXM1 was expressed in the nucleus and cytoplasm of OSCC tissues samples. There was a significant association between FOXM1 expression in tumor tissues and N classification (P=0.0395), stage (P=0.004), therapeutic efficacy (P=0.0113) and outcome (P=0.0134) of patients. However, FOXM1 expression had no association with patients' sex, age or T classification. Additionally, high expression of FOXM1 in tumor cells was associated with a shorter overall survival (P=0.0257) of patients. Multivariate analysis also revealed that elevated expression of FOXM1 was a predictor of patients' poor survival (P=0.0327). The results suggested that high expression of FOXM1 in OSCC tumors may result in reduced therapeutic effects and poor clinical outcomes of patients receiving Doc-based treatment regimens.